Oral and Dental Manifestations of Diamond-Blackfan Anemia: Case Reports - Ozden, Feyza Otan (Dental Investigations Society, 2011)
Diamond-Blackfan Anemia (DBA) is a red cell aplasia characterized with physical abnormalities. The incidence of the disease is reported to be five to seven (5–7) cases per million births in Europe and 4–5 per million live births in the UK and Netherlands with equal sex ratio. It was first recognized in 1938 but an exact pathophysiology of the disease has not been described yet. These abnormalities are well known, however, detailed oral and dental conditions related with the disease have not been described previously. We herein presented two cases of DBA together with oral and dental findings. Our study is first to report the gingival status of the patients with a complete investigation of any orthodontic or dental abnormalities in these kind of patients. A careful follow up and preventive therapies should not be missed in these kind of patients.